ANALISIS PENGARUH SIZE, EQUITY ASSET RATIO (EAR), NIM, LDR, NPL, DAN BIAYA OPERASI TERHADAP PROFITABILITAS BANK (Studi pada Bank Umum Go Public Indonesia, Malaysia, Philipina, Singapore dan Thailand Periode 2012-2016) - Simbolon, Tioro; Demi Pengestuti, Irene Rini (Diponegoro Journal of Management, 2017)
Financial performance has become one of the considerations about the condition of a bank. Many factors affect the financial performance of a bank. Therefore, this study examines the effect of Size, Equity To Asset Ratio (EAR), Net Interest Margin (NIM), Loan Deposoit Ratio (LDR), Non Performing Loan (NPL) and Operating Costs to Profitability of public banks go public ASEAN-5 (Indonesia , Malaysia, Philippines, Singapore and Thailand) 2012-2016.The sample used in this study are commercial banks go public in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore and Thailand). The sampling technique is purposive sampling with certain criteria that is banking company whose financial report has been published in Bloomberg in period 2012-2016. Then obtained a sample of 47 commercial banks go public in ASEAN-5. The method used in this research is multiple regression analysis with panel data. by using the F test and t test.The result of regression analysis at commercial banks of go public ASEAN-5 (Indonesia, Malaysia, Philippine, Singapore and Thailand) shows Size has positive and significant influence to ROA, EAR have positive influence and significant to ROA, NIM have positive effect to ROA, LDR has negative and significant Against ROA, NPL has a negative and significant impact on ROA, Operating Cost negatively affects ROA. The adjusted value (R2) is 0.728. This shows that the influence of independent variables on ROA in commercial banks go public ASEAN-5 (Malaysia, Philippines, Singapore and Thailand) of 72.8% while the rest is influenced by other factors. The result of statistic test t only on public bank go public Indonesia shows that Size has positive and significant effect to ROA, EAR has positive and insignificant effect to ROA, LDR has negative and significant influence to ROA, NPL has negative effect on ROA , Operating Cost negatively affects ROA. The adjusted value (R2) obtained by 0.810% indicates that the large independent influence on ROA on the category of public bank go public Indonesia is 81.0% while the rest is influenced by other factors. The test result only on public bank of go public Non Indonesia (Malaysia, Philippines, Singapore and Thailand) show Size have positive influence and significant to ROA, EAR have positive effect not significant to ROA, NIM have positive effect to ROA, LDR have negative effect and signifikan to ROA, NPL negatively affects ROA, Operating Cost negatively affects ROA. The adjusted value (R2) is 0.265%. This shows that the influence of independent variables on ROA of public banks go public Non Indonesia (Malaysia, Philippines, Singapore and Thailand) is 26.5% while the rest is influenced by other factors.